The complete chloroplast genome of Ensete glaucum (Roxb.) Cheesman - Nguyen, H. D.; Le, V. M.; Nguyen, P. A. T.; Dinh, H. N.; Phan, N. H.; Vu, M. T.; Do, H. D. K. (International Journal of Agricultural Technology, 2022)
Ensete glaucum (Roxb.) Cheesman, also called snow banana, originated in Asia and has ornamental and medicinal value. Results found its complete chloroplast genome, which is 168,483 bp in length and composed of a large single-copy region (LSC; 88,233 bp), a small single-copy region (SSC; 11,138 bp), and two inverted repeat regions (IR; 34,636 bp). The completely sequenced genome includes 135 coding regions of 87 protein-coding genes, 40 tRNAs, and 8 rRNAs. An analysis of repeat composition identified 31 simple sequence repeats and 44 long repeats, mostly in non-coding regions. Notably, the ycf1 and ycf2 genes contain various repeats within the coding sequences. A maximum likelihood phylogenetic analysis revealed a close relationship between E. glaucum and Musella lasiocarpa rather than Musa species. Within E. glaucum, the Vietnam sample had a chloroplast genome more similar to a sample from Taiwan than the Indian variety